Optimasi Daya Hisap LTDS 1 dan LTDS 2 dalam Upaya Penurunan Losses Kernel Menggunakan Metode Reliability Centered Maintenance, Failure Mode and Effect Analysis, dan Statistical Process Control - Dea Anggi Persada Sinaga; Erikson Daniel Sihombing; Albert Winata; Anita Christine Semibiring (MODELING: Jurnal Program Studi PGMI, 2026)
Kernel losses are the main problem in the palm oil processing process because they have a direct impact on the company's yield and losses. The high kernel losses in the Palm Oil Mill are caused by the ineffectiveness of the suction power on LTDS 1 and LTDS 2 which results in the kernel and shell separation process not running optimally. This research aims to optimize the suction power of LTDS 1 and LTDS 2 using the Reliability Centered Maintenance (RCM), Failure Mode and Effect Analysis (FMEA), and Statistical Process Control (SPC) methods. Initial results show that LTDS 1 has lower suction power and higher kernel losses than LTDS 2, and the separation process is not yet statistically stable. Based on the results of the RCM and FMEA analysis, improvements were made to the fan and ducting systems, as well as implementing scheduled preventive maintenance. The final results show an increase in the suction power of LTDS 1 by 2.15% and LTDS 2 by 1.51%, which is followed by a decrease in kernel losses and more controlled process conditions based on SPC analysis. These results show that the integration of RCM, FMEA, and SPC methods is effective in improving LTDS performance and reducing kernel losses in a sustainable manner.